Identification of Sponge-Associated Bacteria From the Coast of Kuwait and Their Potential Biotechnological Applications - Abbas, Shahad; Mahmoud, Huda (Frontiers in Microbiology, 2022)
Sponges are among the most ancient animals harboring complex microbial communities with potential applications in biotechnology. The Arabian Gulf is a thermally stressed enclosed body of water located in an arid region where sponges and their halobionts are understudied. This study combined 16S rRNA next-generation gene amplicon sequencing and cultivation techniques to explore the abundance and diversity of sponge-associated bacteria. Culture-independent techniques showed the associations of more than 25 bacterial phyla with Amphimedon sp., Chondrilla australiensis, Haliclona sp., and Niphates spp. Regarding cultivable bacteria, 315 bacterial isolates associated with the sponge Haliclona sp. were cultivated; these isolates were affiliated with the phyla Proteobacteria and Firmicutes and were distributed among six bacterial genera. Selected strains of Bacillus, Ferrimonas, Pseudovibrio, Shewanella, Spongiobacter, and Vibrio were tested for antimicrobial activity against indicator microorganisms and protease enzyme production. Seven Bacillus strains exhibited weak to moderate growth inhibition against Bacillus subtilis, Staphylococcus aureus, and Candida albicans. Furthermore, 29 different strains of Bacillus, Ferrimonas, Shewanella, and Vibrio exhibited different degrees of positive protease activity. In addition, cultivated strains of Bacillus, Shewanella, Pseudovibrio, and Vibrio were tested for their biomineralization abilities. Herein we report for the first time the isolation of biomineralizing bacteria from sponge tissue where eleven bacterial isolates produced different shapes of calcium carbonate crystals on agar. Our observations shed light on the diversity and biotechnological potentials of sponges-associated bacteria inhabiting one of the world's hottest seas.